2018
DOI: 10.7554/elife.36375
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent kinase control of motile ciliogenesis

Abstract: Cycling cells maintain centriole number at precisely two per cell in part by limiting their duplication to S phase under the control of the cell cycle machinery. In contrast, postmitotic multiciliated cells (MCCs) uncouple centriole assembly from cell cycle progression and produce hundreds of centrioles in the absence of DNA replication to serve as basal bodies for motile cilia. Although some cell cycle regulators have previously been implicated in motile ciliogenesis, how the cell cycle machinery is employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 50 publications
2
31
2
Order By: Relevance
“…In the case of RIBC2 , which is known to function within the cell cycle (Giotti et al, 2018), the gene also influences motile ciliary beating in Chlamydomonas , where it has shown to colocalized to the axoneme (Chung et al, 2014). Such findings of multifunctional genes add to the emerging literature on the alternative regulation of centrosomal and cell cycle genes for motile- and multi-ciliogenesis or associated with their function, as also suggested by their coexpression with FOXJ1 across tissue from the GTEx (Vladar et al, 2018, Zhao et al, 2013, Balestra and Gönczy, 2014). Indeed, studies have found certain cell cycle genes uniquely regulated through alternative promoter usage depending on the cell type (Giotti et al, 2018).…”
Section: Discussionsupporting
confidence: 56%
“…In the case of RIBC2 , which is known to function within the cell cycle (Giotti et al, 2018), the gene also influences motile ciliary beating in Chlamydomonas , where it has shown to colocalized to the axoneme (Chung et al, 2014). Such findings of multifunctional genes add to the emerging literature on the alternative regulation of centrosomal and cell cycle genes for motile- and multi-ciliogenesis or associated with their function, as also suggested by their coexpression with FOXJ1 across tissue from the GTEx (Vladar et al, 2018, Zhao et al, 2013, Balestra and Gönczy, 2014). Indeed, studies have found certain cell cycle genes uniquely regulated through alternative promoter usage depending on the cell type (Giotti et al, 2018).…”
Section: Discussionsupporting
confidence: 56%
“…Another study found that CDK2, the kinase responsible for G1-S phase transition, was also required in MCC to initiate the motile ciliogenesis program independent of cell cycle progression 47 . Thus, 11 one possible reason for the elevated Plk4 protein is to coordinate the timing of centriole assembly and maturation in post-mitotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…This amplification occurs through the formation of intermediate organelles, the deuterosomes, which are composed of centrosome-related elements 2,3 . Deuterosomes support massive centriole production within a molecular cascade that is shared with the cell cycle centrosome duplication program [3][4][5] . Because two centrosomal centrioles seemed insufficient to scaffold the formation of tens of centrioles, massive centriole production through deuterosome structures was proposed to arise independently from the centrosome in MCC 6 .…”
Section: Introductionmentioning
confidence: 99%